Progress on OECD Chemicals Programme (9): SIAM 17 in Arona, 2003 - Kanno, Seiichirou; Sugaya, Yoshio; Takahashi, Mika; Kawahara, Kazumi; Hirose, Akihiko; Kamata, Eiichi; Matsumoto, Mariko; Ema, Makoto (ChemoBio Integrated Management, 2006)
The 17th Screening Information Data Set (SIDS) Initial Assessment Meeting (SIAM 17) was held in Arona, Italy, hosted by the European Commission. The initial assessment documents of six substances (CAS numbers: 96-29-7, 118-79-6, 461-58-5, 611-19-8, 6165-51-1, 12125-02-9) at SIAM 17 were submitted by the Japanese Government with or without the International Council of Chemical Associations (ICCA) and all of them were agreed at the meeting. In this report, the documents of these substances are introduced.